2019
DOI: 10.1111/petr.13455
|View full text |Cite
|
Sign up to set email alerts
|

Publication trends in pediatric renal transplantation: Bibliometric analysis of literature from 1950 to 2017

Abstract: Introduction Pediatric renal transplantation has been heavily published since the 1950s. Herein, we describe the bibliometrics and impact of the 200 most‐cited pediatric renal transplantation manuscripts. Methods We identified pediatric renal transplantation publications from 1900 onwards. Year, citations, h‐index, geographic origin, impact factor, topic, and design of the 200 top‐cited papers were extracted. Impact index was calculated, adjusting for citation volume and time since publication. Results Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Also, there is no prior evidence suggesting AP technique is superior to TA techniques in RT which makes the present study novel, adding to the very limited body of evidence pertaining to surgical aspects within the field of pediatric RT. 20 Given that we found no difference in these parameters when comparing underlying ESRD causes and donor type, it is suggestive that anastomosis technique is the driving factor. Further follow-up may shed light on the clinical impact of improved early perfusion on long-term graft function.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Also, there is no prior evidence suggesting AP technique is superior to TA techniques in RT which makes the present study novel, adding to the very limited body of evidence pertaining to surgical aspects within the field of pediatric RT. 20 Given that we found no difference in these parameters when comparing underlying ESRD causes and donor type, it is suggestive that anastomosis technique is the driving factor. Further follow-up may shed light on the clinical impact of improved early perfusion on long-term graft function.…”
Section: Discussionmentioning
confidence: 74%
“…Despite these limitations, our paper has several strengths including a large RT database allowing for selection of appropriately matched controls for comparisons. Also, there is no prior evidence suggesting AP technique is superior to TA techniques in RT which makes the present study novel, adding to the very limited body of evidence pertaining to surgical aspects within the field of pediatric RT 20 . Given that we found no difference in these parameters when comparing underlying ESRD causes and donor type, it is suggestive that anastomosis technique is the driving factor.…”
Section: Discussionmentioning
confidence: 77%
“…In line with the findings of others, North American and European countries were most productive in publishing on EA worldwide. 10,11 This might be explained by the high socioeconomic development of these countries. Huffman and his group showed that high-income countries accomplished more output of research, while low-and middleincome countries had only less scientific contributions.…”
Section: Networking Promotes Quantity and Quality Of Publicationsmentioning
confidence: 99%
“…Thus, research trends, striking journals, active countries, authors, institutions, as well as global collaborations can be identified. 9,10 To elucidate the quantitative and qualitative scientific output, hot topics, and collaboration of research in EA, we performed a comprehensive bibliometric study on the existing peer-reviewed literature of the past 74 years.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analyses can also be applied to several papers within a specific field, to judge the relative impact of each paper in that field. In this issue of the journal, Rickard et al have performed, to this editorial author's knowledge, the first ever such bibliometric analysis of papers published in the field of pediatric kidney transplantation, between 1950 and 2017 . They have created a list of the top 200 most cited papers.…”
mentioning
confidence: 99%